(untitled) (Global Journal of Management and Business Research, 2012)
Value chain analysis is essential to an understanding of markets, their relationships, the Participation of different actors, and the critical constraints that limit the growth of livestock production and consequently the competitiveness of smallholder farmers. These farmers currently receive only a small fraction of the ultimate value of their output, even if, in theory, risk and rewards should be shared down the chain. Objective : Main objective of the study is to evaluate the effectiveness of the paddy field#x2019;s value chain in the karachchi division, Kilinochchi district. And environs with a view to achieving the following broad output, to identify the key value chain actors in the paddy sector; to find out key factors influencing on value chain analysis for paddy sector; to discover the strengths and weakness of each value chain actors; to discover the opportunities and threats of each value chain actors; finally to suggest the value chain actors to strengthening the paddy sector in accordance with benefits of socio and economic point of view.